PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA MELAKUKAN USAHA PENAMBANGAN TANPA IZIN IUP, IPR ATAU IUPK BERDASARKAN PASAL 158 UNDANG-UNDANG NOMOR 3 TAHUN 2020 TENTANG PERTAMBANGAN MINERAL DAN BATU BARA (Studi Putusan Nomor : 518/Pid.Sus/2022/Pn.Tjk) - Lukmanul Hakim; Alma Zhuhri Febriansyah; Aprinisa (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
Mining is all or part of the stages of activity in the management and exploitation of minerals or coal which includes exploration, feasibility studies, construction, mining, management & refining, transportation & sales, and post-mining activities. As for what is the dispute in this study, how is the responsibility of the perpetrators of criminal acts in conducting a mining business without IUP, IPR or IUPK Permits & How to consider the rules of the Panel of Judges in determining the crime of carrying out a mining business without IUP, IPR or IUPK Permits from Study Decision Number: 518 /Pid.Sus/2022/ PN.Tjk? the research method used is normative & empirical juridical, the output of research on criminal liability for conducting mining business without a permit is imprisonment for 2 (two) months & 15 (fifteen) days & a penalty of IDR 5,000,000.00 (5 million rupiah) And the legal considerations of the Panel of Judges in determining the criminal act of conducting a mining business are not yet perfect because it is too light for the perpetrators who have committed mining crimes without causing environmental damage as a result, as a result of which they cannot have a deterrent effect on the perpetrators.